EFFECT OF USING CUE CARDS TO IMPROVE STUDENTS’ SKILLS IN WRITING DESCRIPTIVE TEXTS AT THE TENTH GRADE STUDENTS OF MA MA’ARIF 06 PASIR SAKTI - Siti Ulfa Khusniyah; Deri Sis Nanda (Universitas Bandar Lampung, 2016)
The objective of this research is to find whether there is effect or not of using cue cards to improve students’ skills in writing descriptive texts for the tenth grade students of MA Ma’arif 06 Pasir Sakti. The research method was experimental class which conducted between the students of X IPS 1 and X IPS 2 as the subject. The tenth grade of IPS 1 was taught using cue cards while the tenth grade of IPS 2 was taught without using cue cards. Based on the result of data analysis, the research findings are: (1) The cue cards is more effective for teaching writing descriptive text than without using cue cards for tenth grade students of MA Ma’arif 06 Pasir Sakti; (2) The students’ writing was improving after cue cards was applied. It can be concluded that cue cards is an effective media used to improve the writing skill of the tenth grade students of MA Ma’arif 06 Pasir Sakti.